Kajian Literatur: Pengetahuan dan Perilaku Kesehatan Reproduksi pada Keluhan Flour Albus Patologis - Aida Musyarrofah; Nafia Prasetyo; Ruby Riana Asparini (ARTERI : Jurnal Ilmu Kesehatan, 2023)
Pathological fluor albus is a reproductive problem experienced by women. Reproductive health and sexuality education (KRS) is considered to be one of the solutions to this problem. Comprehensive Sexuality Education (CSE) is an international education program about KRS. This study aims to determine the aspects of knowledge and behavior in reproductive health in pathological fluor albus complaints. This research is a literature review. References were taken from 14 textbooks published in the last 10 years and 34 journals with Scopus Q1 and Q2 indexes and 1 Sinta 2 accredited journal published in the last 5 years. Some articles mention that lack of reproductive health knowledge and poor personal hygiene increase a person's risk of experiencing pathological fluor albus. Providing KRS education and how to clean the genitals properly can improve the quality of personal hygiene which further reduces the risk of pathological fluor albus. Other KRS points in CSE such as how socio-economic, cultural, and health services can have an effect on the quality of one's health are assumed to have an impact on one's health knowledge and behavior. This can increase or decrease a person's risk of experiencing pathological fluor albus. Understanding of pathological fluor albus is influenced by knowledge and behavior in reproductive health